Sosialisasi Pemanfaatan dan Pengenalan Aplikasi Canva dalam Meningkatkan Kreativitas dan Literasi Digital Siswa SMPN 7 Bintan - Desti Natalia; Susanti Susanti; Nur Alizah; Fitri Andini; Nuranisa Nadiya; Siti Patimah; Azahra Ashilah; Eki Pauziansah; Ihqsan Akbar (BADAN PENERBIT STIEPARI PRESS, 2025)
Digital technology has highlighted the importance of developing students' creativity and digital literacy. This study aims to enhance the skills of eighth-grade students at SMPN 7 Bintan in using Canva as a creative learning tool. The community service program involved 30 students in participatory activities that encouraged active engagement in socialization, digital media creation, and academic presentations. The program was designed to familiarize students with Canva’s features, such as the dashboard, templates, and multimedia elements, to improve their skills in creating interactive and visually appealing content. The results showed significant improvements in students’ technical skills, including proficiency in using the Canva dashboard, creating interactive and visual media, and boosting their confidence in utilizing digital tools. Furthermore, students responded positively to Canva-based learning, as evidenced by increased motivation, better understanding of the material, and active participation in class activities. The integration of Canva into the curriculum fostered creativity, teamwork, and digital literacy, demonstrating that it is an effective and engaging teaching model for 21st-century education. This approach not only improved students’ practical digital skills but also enhanced their ability to communicate and collaborate using modern digital platforms. These findings suggest that incorporating Canva-based digital media into education can significantly contribute to student engagement and learning outcomes, especially in the digital age.